Método de Soluciones Particulares Aproximadas Para la Solución de Fluidos Electro-Cinéticos en Micro y Nanocanales - Castro, D.A.; Flórez, W.F.; Caruso, N.; Portapila, M. (TECCIENCIA, 2020)
This paper presents an application of the method of approximate particular solutions with radial basis functions (MAPS) in two dimensions, for the solution of electrokinetic flows in micro and nanochannels. This development is performed for a mixed electroosmotic flow and driven by a pressure gradient. The implementation of the method is carried out for a rectangular micro channel, in two dimensions and for a cylindrical nanochannel. The results obtained show the MAPS implementations, their directness and simplicity whenapplied to the models presented here, allowing to obtain good approximations using few nodes.